International emissions trading in a non-cooperative equilibrium - Bjart J. Holtsmark; Dag Einar Sommervoll (Statistics Norway, Research Department, 2008)
Linkage of different countries' domestic permit markets for pollution rights into a single international market alters governments' incentives, and may trigger adjustments of the number of allocated permits. First, this work finds that in a non-cooperative equilibrium, international emissions trading is likely to increase the total emissions. Second, although trading will give a more efficient cross-country allocation of emissions, efficiency may nevertheless fall, because an already inefficiently low abatement level is likely to be further reduced. Third, we find that large countries are likely to experience losses from linking their permit markets to the permit markets of smaller countries.
Keywords: C72; F53; Q54; 330; Emissions trading; efficiency; non-cooperative games